An Analysis of Word Formation Processes in William Shakespeare's poetries - M. Yusril Rizqi Hidayat; Alfiyana Ni’mah Fadhila (Universitas Sebelas Maret, 2024)
This study aims to analyze the types of word formation processes in three poems of William Shakespeare entitled